Women's Electoral Success and Female Voter Turnout: Evidence From Individual Voting Data for Germany. - Neugart, Michael; Zuazu, Izaskun (Kyklos, 2025)
This paper brings individual‐level evidence to the hypothesis that women holding political offices, that is, descriptive representation, affects the participation of women in politics. Specifically, using a regression discontinuity design, we analyze the role of close victories of directly elected female candidates in mixed‐gender races at the federal elections in Germany in 2013 on individuals' decisions to turn out at the federal elections in Germany in 2017. We account for mediating channels such as changes in the pool of candidates, policy outcomes, policy interest, and knowledge that may all also affect voter turnout. The results indicate no effect of descriptive representation on female turnout in the future.